Organolead(IV) Complexes with O- and N-Donor Ligands - Sharma, R.; Nath Pandey, Gajendra; Sharma, S.N.; Ranjan, Rajeev; Kumar, Praveen (Asian Journal of Chemistry, 2010)
Organolead(IV) complexes of monobasic triazene-1-oxides have been synthesized and chacacterised by various physico-chemical techniques. The results have been found invariably to conform to R2PbT2. The disposition of two alkyl groups whether cis-or trans-were ascertained through the infra-red spectral bands of lead-carbon bond of the alkyl groups. It has been found that whereas the methyl group occupy cis-position while the bulkier alkyl groups occupy trans-positions.